2007
DOI: 10.1152/ajpregu.00909.2006
|View full text |Cite
|
Sign up to set email alerts
|

High-altitude chronic hypoxia during gestation and after birth modifies cardiovascular responses in newborn sheep

Abstract: Perinatal exposure to chronic hypoxia induces sustained pulmonary hypertension and structural and functional changes in both pulmonary and systemic vascular beds. The aim of this study was to analyze consequences of high-altitude chronic hypoxia during gestation and early after birth in pulmonary and femoral vascular responses in newborn sheep. Lowland (LLNB; 580 m) and highland (HLNB; 3,600 m) newborn lambs were cathetherized under general anesthesia and submitted to acute sustained or stepwise hypoxic episod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
144
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(159 citation statements)
references
References 38 publications
13
144
1
1
Order By: Relevance
“…This was a surprise, because chronic hypoxia generally increases pulmonary arterial pressure and depresses pulmonary arterial vasodilatory capacity, as was observed in the newborn (Fig. 2D) and in previous studies (40). The findings suggest that fetal sheep adapt in utero to compensate for eventual birth in a highaltitude, low-O 2 environment.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This was a surprise, because chronic hypoxia generally increases pulmonary arterial pressure and depresses pulmonary arterial vasodilatory capacity, as was observed in the newborn (Fig. 2D) and in previous studies (40). The findings suggest that fetal sheep adapt in utero to compensate for eventual birth in a highaltitude, low-O 2 environment.…”
Section: Discussionsupporting
confidence: 71%
“…2D). This loss could potentially contribute to the elevation in pulmonary pressures and increases in pulmonary vascular resistance that we and others have documented in lambs born at high altitude (10,40). Furthermore, it is possible that the prenatal acceleration of vasorelaxation responses to bradykinin is redistributing blood flow from developing vital organs to the lung, resulting in blood flow distribution issues.…”
Section: Discussionmentioning
confidence: 83%
“…However, data in the present study show that in vivo assessment in adult offspring from hypoxic pregnancy provides no evidence of either an increase in peripheral vascular resistance or systemic hypertension. This finding is corroborated by further evidence of no hypertension in highland residents, 40 neonatal sheep from high altitude pregnancy, 35 adult chickens subjected to hypoxia in ovo, 32 or adult rats following prenatal hypoxia. 37, 41 Despite no evidence of any changes in basal arterial blood pressure, this study revealed significant programming on the autonomic control of arterial blood pressure in adult offspring Values are mean ± SEM for baroreflex function in 4-month-old male offspring from Normoxic (N; n=8), Hypoxic (H; n=9), Hypoxic+Vitamin C (HC; n=7) and Normoxic+Vitamin C (NC; n=7) pregnancies.…”
Section: Discussionmentioning
confidence: 53%
“…8, 29 Secondly, this level of maternal hypoxia induces fetal hypoxia of 10-13 mmHg, 30 which is equivalent to PO2 measured in human umbilical blood taken by cordocentesis in IUGR complicated pregnancies. 31 Several previous studies in many species and at different stages of life, including reports in the chick embryo, 14,32,33 the sheep fetus, 34 the newborn lamb 35 and the adult rat 12,36-39 have consistently shown that exposure to chronic developmental hypoxia leads to increases in sympathetic innervation, greater α1-adrenoreceptor-mediated vasoconstriction and decreased NO-dependent vasodilatation in the peripheral vasculature. Collectively, the data suggest that chronic developmental hypoxia induces a peripheral vasoconstrictor phenotype, which might contribute to a fetal origin of hypertension in later life.…”
Section: Discussionmentioning
confidence: 96%
“…Neonatal pulmonary hypertension in humans is associated with developmental chronic hypoxia and results in high mortality, decreased postnatal growth and long lasting neurological, respiratory, and cardiac complications (4,10,14,21,45). We have developed a model of neonatal pulmonary hypertension in sheep, gestated and born at high altitude in the Andean Altiplano, characterized by an increased PAP, impaired vascular reactivity, and altered arterial structure in the pulmonary circulation (14,15,16,18).…”
mentioning
confidence: 99%